Female breast cancer in Świętokrzyskie Voivodeship in 1999–2012. New cases and the incidence of invasive breast cancer - Ewa Błaszkiewicz; Stanisław Głuszek; Halina Król; Małgorzata Terek-Derszniak; Paweł Macek; Stanisław Góźdź (Studia Medyczne, 2015)
Introduction : Breast cancer is the most common malignant tumour among women in Poland. In 2012 invasive breast cancer was diagnosed in 17,000 Polish women. The effective fight against breast cancer is based on activities to prevent its occurrence or to enable early detection of the disease and then its effective treatment (cure). Aim of the research: To assess the prevalence of invasive breast cancer in women in Świętokrzyskie Voivodeship in 1999–2012. Material and methods: A total of 6079 new female invasive breast cancer cases were analysed. Crude rates (CRs) and age-standarised rates (ASRs) per 100,000 population were calculated. The total value of incidence rates was analysed for all ages (0–85+) and in separate age groups (15–49, 50–69, and 70–85+). Results : In 1999–2012 in Świętokrzyskie Voivodeship 6079 new invasive female breast cancer cases were diagnosed. Fifty-three percent of them were in the age group of 50–69 years, 25.0% in the age group 70–85+, and 21.5% in the age group 15–49 years. The incidence of BC in general (0–85+) increased from 41.2/105 in 1999 to 43.8/105 in 2012. In the women aged 15–49 years the value of ASRs of incidence increased. In the age group of 50–69 years the value of ASRs increased from 146.6/105 in 1999 to 163.5/105 in 2012. The increase in the incidence of breast cancer was reported among women in perimenopausal age and in premenopausal women. The decrease in breast cancer cases was observed among young, premenopausal women (15–49 years) as well as among women over 70 years of age. Conclusions: Świętokrzyskie Voivodeship is a region in Poland with moderate risk of breast cancer.